New concepts in follicular lymphoma biology: From BCL2 to epigenetic regulators and non-coding RNAs - Devan, Jan; Janikova, Andrea; Mraz, Marek (Seminars in oncology, 2018)
The molecular pathogenesis of follicular lymphoma (FL) was partially revealed 3 decades ago, with the discovery of the translocation that brings BCL2 under the influence of immunoglobulin heavy chain enhancers in a vast majority of cases. Despite the importance of this seminal observation, it has become increasingly clear that additional genetic alterations need to occur to trigger neoplastic transformation and disease progression. The evolution of FL involves developmental arrest and disruption of the normal function of one or more of epigenetic regulators including KMT2D/MLL2, EZH2, CBP/CREBBP, p300/EP300, and HIST1H1 in >95% of cases. B-cells "arrested" in germinal centers acquire dozens of additional genetic aberrations that influence key pathways controlling their physiological development including B Cell Receptor (BCR) signaling, PI3K/AKT, TLR, mTOR, NF-κB, JAK/STAT, MAPK, CD40/CD40L, chemokine, and interleukin signaling. Additionally, most cases of FL do not result from linear accumulation of genomic aberrations, but rather evolve from a common progenitor cell population by diverse evolution, creating multiple FL subclones in one patient. Moreover, one of the subclones might acquire a combination of aberrations involving genes controlling cell survival and proliferation including MDM2, CDKN2A/B, BCL6, MYC, TP53, β2M, FOXO1, MYD88, STAT3, or miR-17-92, and this can lead to the transformation of an initially indolent FL to an aggressive lymphoma (2%-3% risk per year). The complexity of the disease is also underscored by the importance of its interactions with the microenvironment that can substantially influence disease development and prognosis. Interpreting individual aberrations in relation to their impact on normal processes, their frequency, position in the disease evolution, and the consequences of their (co)occurrence, are the basis for understanding FL pathogenesis. This is necessary for the identification of patients with risk of early progression or transformation, for the development of novel targeted therapies, and for personalized treatment approaches. In this review, we summarize recent knowledge of molecular pathways and microenvironmental components involved in FL biology, and discuss them in the context of physiological B-cell development, FL evolution, and targeted therapies.
Keywords: signální transdukce; epigeneze genetická; lidé; regulace genové exprese u nádorů; Epigenesis, Genetic; Transformation; nekódující RNA; Signal Transduction; Lymphoma, Follicular; miRNA; RNA, Untranslated; zvířata; Humans; Gene Expression Regulation, Neoplastic; Proto-Oncogene Proteins c-bcl-2; BCR signaling; Tumor microenvironment; biologické markery; receptory antigenů B-buněk; Epigenetics; Follicular lymphoma; Receptors, Antigen, B-Cell; Biomarkers; folikulární lymfom; protoonkogenní proteiny c-bcl-2; Animals